Investigation of Passive Voice Occurrence in Scientific Writing - Urip Subagio; J. A. Prayogo; Emalia Iragiliati (International Journal of Language Teaching and Education, 2019)
This study investigated passive voice use in theses of Graduate EFL students, Universitas Negeri Malang. The occurrences of passive voice in research method chapter in two time periods, 1985 - 2000 and 2002 – 2015 were compared. Passive voice occurrence in chapter of research method was also investigated then it was compared with the active. Passive voice occurrence in theses before 2002 investigated which was 1458, and 1171 in theses published after 2000 indicated the fact that today passive voice use in scientific writing indeed less frequent compared to the past. In addition, unlike the findings of some previous studies that claimed passive voice occurrence is still more dominant than the active in method section of scientific writing, this study found that, even in chapter of research method, active voice today occurs more frequently. It was 1883 occurrences of active voice and 1171 of passive voice were found.